2018
DOI: 10.14740/gr1021w
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Underwater Endoscopic Mucosal Resection for Colorectal Lesions: A Single Center Study in Japan

Abstract: BackgroundUnderwater endoscopic mucosal resection (U-EMR) has emerged as an alternative technique for the resection of colorectal lesions. This study aimed to evaluate our initial experience using U-EMR.MethodsThis is a single-center, retrospective case series study. We analyzed the clinical outcomes of consecutive patients who underwent U-EMR in our endoscopy center, from December 2015 to February 2017.ResultsOur analysis included 64 lesions, contributed by 38 patients, with a mean age of 68.6 years (range, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 21 publications
1
41
1
2
Order By: Relevance
“…In addition, delayed hemorrhage occurred in two patients in the CEMR group, with no patient with this clinical complication in the UEMR group. Our findings were consistent with three previous studies: one reported a delayed bleeding rate of 5% [ 11 ], one described a rate of 6.7% [ 12 ], and one of 0% [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, delayed hemorrhage occurred in two patients in the CEMR group, with no patient with this clinical complication in the UEMR group. Our findings were consistent with three previous studies: one reported a delayed bleeding rate of 5% [ 11 ], one described a rate of 6.7% [ 12 ], and one of 0% [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…47,69 The use of innovative techniques such as underwater EMR might present larger resection surfaces, as this technique relaxes the bowel wall, leading to larger resection specimens and the potential to achieve wider resection margins and IRR reduction. 41,70 Important studies addressing these questions are currently being performed (NCT03462706, NCT03833492). 71,72 Our study found that margin biopsies are often positive even after visual inspection of the resection site indicates complete resection.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies [9,11,23,26,[28][29][30]32], including 431 colorectal polyps, focused on R0 resection, of which 267 were removed by R0 resection ( Table 7s). The pooled UEMR-related R0 resection rate was 60.9 % (95 %CI 52.3 %-69.6 %) with a high level of heterogeneity (I 2 = 69 %, P < 0.01) for the resection of ≥ 10-mm polyps (▶ Fig.…”
Section: R0 Resection Ratementioning
confidence: 99%
“…Six studies [9,11,26,28,30,32], comprising 238 colorectal polyps, and six studies [ ▶ Fig. 1 Forest plots of the rates of: a overall adverse events; b bleeding; c perforation; d post-polypectomy syndrome; e adverse events in polyps of 10-19 mm; f adverse events in polyps of ≥ 20 mm.…”
Section: R0 Resection Ratementioning
confidence: 99%